The Iconography Of Sema Stones In Dvaravati Art Of LAO PDR (Journal of Namibian Studies : History Politics Culture, 2023)
This article is a part of the study on model iconography and distribution of Sema stones in the Dvaravati-art of Lao PDR. The purpose of this study was to study the iconography of Sema stones in the Dvaravati-art of Lao PDR. A survey and study of Sema stones in Dvaravati-art of Lao PDR. revealed 2 characteristics of carved images: 1) Symbolic images such as the lotus band motif and the Stupa-Kumpha motifs; 2) Auspicious images such as portraits and narrative arts. All of these symbols are associated with both Theravada and Mahayana Buddhism. Theravada and Mahayana Buddhism share symbols, such as lotus petals and lotus flowers, which symbolize the Buddha. The Stupa-Kumbha is a mixed Buddhist symbol, representing the life of Lord Buddha and abundance and liberation. Auspicious images include engraved group portraits, single portraits, and three Buddha jatakas: Vidhurapandita Jataka, Mahosadha Jataka, and Kulavaka Jataka. These images reflect the values and worldviews of the time, reflecting the values and worldviews of the people.